Increase of aerobic glycolysis mediated by activated T helper cells drives synovial fibroblasts towards an inflammatory phenotype: new targets for therapy? - Kvacskay, Peter (2021)
A dysregulated glucose metabolism in synovial fibroblasts (SF) has been associated with their aggressive phenotype in rheumatoid arthritis (RA). Even though T helper (Th) cells are key effector cells in the propagation and exacerbation of synovitis in RA, little is known about their influence on the metabolism of SF. Thus, this study investigates the effect of Th cells on the glucose metabolism and phenotype of SF and how this is influenced by the blockade of cytokines, janus kinases (JAKs) and glycolysis. Methods: SF from patients with RA or osteoarthritis (OA) were cultured in the presence of a stable glucose isotopomer ([U-13C]-glucose) and stimulated with the conditioned media of activated Th cells (ThCM). Glucose consumption and lactate production were measured by proton nuclear magnetic resonance (1H NMR) spectroscopy. Cytokine secretion was quantified by ELISA. The expression of glycolytic enzymes was analysed by PCR, western blot and immunofluorescence. JAKs were blocked using either baricitinib or tofacitinib and glycolysis by using either 3-bromopyruvate or FX11. Results: Quiescent RASF produced significantly higher levels of lactate, interleukin (IL)-6 and matrix metalloproteinase (MMP) 3 than OASF. Stimulation by ThCM clearly changed the metabolic profile of both RASF and OASF by inducing a shift towards aerobic glycolysis with strongly increased lactate production together with a rise in IL-6 and MMP3 secretion. Interestingly, chronic stimulation of OASF by ThCM triggered an inflammatory phenotype with significantly increased glycolytic activity compared to unstimulated, singly stimulated or restimulated OASF. Finally, in contrast to cytokine-neutralizing biologics, inhibition of JAKs or glycolytic enzymes both significantly reduced lactate production and cytokine secretion by Th cell-stimulated SF. Conclusions: Soluble mediators released by Th cells drive SF towards a glycolytic and pro-inflammatory phenotype. Targeting of JAKs or glycolytic enzymes both potently modulate SF’s glucose metabolism and decrease the release of IL-6 and MMP3. Thus, manipulation of glycolytic pathways could represent a new therapeutic strategy to decrease the pro-inflammatory phenotype of SF.